Measuring systemic risk in the Southeast Asian banking system: A CoVaR approach - Jónatas, Teresa Silva Galhardo Dutra (2021)
The recent financial crisis has proven how integrated are the economies and the financial markets, and therefore how important is to understand the spillover effects, as well as to measure and manage systemic risk. The Southeast Asian market is no exception, even though little research has been done on systemic risk and contagion in this region. Thus, this dissertation analyzes the cross-sectional dimension of systemic risk in the Southeast Asian banking system, applying Adrian’s and Brunnermeier’s CoVaR methodology to the six major Southeast Asian banks. The results of this dissertation evidence that, over the period between 4th of November 2015 and 1st of November 2019, the banking institutions indeed contribute to the systemic risk of the Southeast Asian financial market; all the banks are sensitive to a systemic crisis; and in fact there are interconnections across them.